CHARACTERISTICS OF ONLINE FOOD DELIVERY SERVICES BASED ON AL-‘UQŪD AL-MURAKKABAH - Ahmad Tholabi; Suparman Suparman; Dyah Ochtorina Susanti; Moh. Ali (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research is based on the fact that injustice is experienced by motorcycle drivers working as couriers for online food delivery (OFD) services. Restaurants and OFD drivers hold very weak positions and are exploited by OFD companies through mechanisms such as the rating system, fake orders, and unfair profit sharing. In this study, the author aims to explore the characteristics of al-‘uqūd al-murakkabah (composite contracts) in online food delivery services. Several characteristics of OFD services based on al-‘uqūd al-murakkabah found in this research are as follows: 1) The contract subjects are the consumers and the service providers, 2) The three service providers are united in a syirkah abdān (partnership of labor), 3) The involved contracts include syirkah abdān, sales (bayʿ), agency (wakālah), and lease (ijārah), 4) Profit distribution is conducted through a revenue-sharing system.